Phenotypic assays for Mycobacterium tuberculosis infection. Issue 10 (19th May 2017) - Song, Ok‐Ryul; Deboosere, Nathalie; Delorme, Vincent; Queval, Christophe J.; Deloison, Gaspard; Werkmeister, Elisabeth; Lafont, Frank; Baulard, Alain; Iantomasi, Raffaella; Brodin, Priscille
Abstract: Tuberculosis (TB) is still a major global threat, killing more than one million persons each year. With the constant increase of Mycobacterium tuberculosis strains resistant to first‐ and second‐line drugs, there is an urgent need for the development of new drugs to control the propagation of TB. Although screenings of small molecules on axenic M. tuberculosis cultures were successful for the identification of novel putative anti‐TB drugs, new drugs in the development pipeline remains scarce. Host‐directed therapy may represent an alternative for drug development against TB. Indeed, M. tuberculosis has multiple specific interactions within host phagocytes, which may be targeted by small molecules. In order to enable drug discovery strategies against microbes residing within host macrophages, we developed multiple fluorescence‐based HT/CS phenotypic assays monitoring the intracellular replication of M. tuberculosis as well as its intracellular trafficking. What we propose here is a population‐based, multi‐parametric analysis pipeline that can be used to monitor the intracellular fate of M. tuberculosis and the dynamics of cellular events such as phagosomal maturation (acidification and permeabilization), zinc poisoning system or lipid body accumulation. Such analysis allows the quantification of biological events considering the host‐pathogen interplay and may thus be derived to other intracellular pathogens. © 2017 International Society for Advancement of Cytometry